2018
DOI: 10.3928/19425864-20180918-01
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Sport Specialization, Running-Related Injury, and Menstrual Dysfunction Among High School Distance Runners

Abstract: To determine the associations between sport specialization, running-related injury, and menstrual dysfunction in high school distance runners. Methods: A total of 126 female runners competing in crosscountry and distance track events in southern California during the 2003-2004 interscholastic sport seasons were prospectively followed. Baseline questionnaires assessed sport participation, menstrual history, demographic characteristics, and anthropometric measurements. Low back and lower extremity musculoskeleta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
21
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 39 publications
1
21
2
Order By: Relevance
“…Since then, sport specialisation at early age has increased globally [99] and participation in organised sport club has become more frequent in Finnish girls [100]. Early sport specialisation can lead to physical and mental harm as it has been linked to reduced motor skill development, increased injury rates, sport dropout, burnout, eating disorders, and menstrual dysfunction [99,[101][102][103]. Thus, generalisability of our results to those who are currently engaged in competitive sport should be done with caution.…”
Section: Limitationsmentioning
confidence: 89%
“…Since then, sport specialisation at early age has increased globally [99] and participation in organised sport club has become more frequent in Finnish girls [100]. Early sport specialisation can lead to physical and mental harm as it has been linked to reduced motor skill development, increased injury rates, sport dropout, burnout, eating disorders, and menstrual dysfunction [99,[101][102][103]. Thus, generalisability of our results to those who are currently engaged in competitive sport should be done with caution.…”
Section: Limitationsmentioning
confidence: 89%
“…All 64 runners underwent a dual-energy x-ray absoptiometry (DXA) scan ( Figure 1). 18,23 These runners were from a larger sample of 170 athletes who participated in 8 interscholastic sports 11,24,25 and completed questionnaires regarding competitive sport involvement and menstrual history. High school athletic directors and coaches in several local high school districts were contacted for approval to allow the research team to approach their runners regarding participation in the study's measures at the beginning of and throughout their interscholastic season.…”
Section: Methodsmentioning
confidence: 99%
“…If the athlete competed in track and field, she was asked to report the number of years and months she competed in distance, sprint, or field events. 23 An athlete was classified as a distance runner if she competed in crosscountry, outdoor track and field distance events (main running event[s]) 1600 m or longer), or both. 23 In this study, each distance runner was placed in 1 of 3 sport-specialization classifications 23 :…”
Section: Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,4,5 MD prevalence rates vary between studies depending on the diagnostic criteria and the population studied, with studies usually investigating only clinically detectable MD. [4][5][6][7][8][9][10][11][12][13][14] Nevertheless, the results of studies comparing the prevalence of MD in athletes and non-athletes have been inconsistent. Hoch et al 12 and Muia et al 6 found that MD was more common in runners and athletes competing in several different sports, respectively, than in sedentary controls.…”
Section: Introductionmentioning
confidence: 99%